The Development of Pre-School Age Children's Acting Skills by Using Short Folklore Texts - Kazragytė, Vida (Acta Paedagogica Vilnensia, 2003)
There are some important reasons to develop children’s creative and acting abilities. When a child without interference by an adult creates an artistic form at the same time he develops various cognitive abilities. Second, an effective arts education is a way to save national culture. And third, through the arts education the humanistic values can be transferred. To develop of pre-school age children’s acting skills we can use communicational education model prepared by us, the sense of which is that a child is not teaching how to act, but is orienting towards acting communication. One of the components of the communicational education model is a literary text of an appropriate structure. Such text could be short folklore text, as it has game elements, dramatic structure, and humanistic values and is rhythmical. A folklore text of a game style stimulates spontaneous satisfactory expression of acting abilities in that case too, when children have not had experience of purposeful educational activity. Game elements help children «to remember» aggregate activity of spirit an unconscious acting abilities which they demonstrate in role playing. Many folklore texts look as as dramatic - they are written in monologue or dialog form and are dynamic. They are also schema tie, so stimulates improvisation of words and dramatic actions. The rhythm helps children easier to enter to the creative situation and better to organize means of acting expression.
Keywords: pre-school age; national culture; folklore; education; acting skills